Marriage as Culmination Rather than Cause: Religious Conversion among Ethnic Chinese in Belitung - Kamsi, Kamsi; Julianto, Very; Billah, Mu'tashim (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
The state guarantees freedom of religious expression for all its citizens, regardless of their beliefs. However, during the New Order era, this freedom was paradoxically curtailed, particularly for individuals of Chinese descent. Chinese Indonesians were prohibited from openly expressing their Chinese identity, including through religious affiliation. They were compelled to reidentify their religion under one of the five officially recognized religions at the time. When it comes to marriage registration, many individuals converted to one of these state-recognized religions. This article sheds light on the extent to which faith and love are intertwined in the phenomenon of religious conversion to Islam in Belitung. Employing a snowball sampling method, we conducted semi-structured interviews with 15 ethnic Chinese individuals from Belitung, aged between 30 and 63 years. These informants were Chinese Indonesians who converted to Islam following the legalization of Confucianism. The results reveal that marriage functioned as a pivotal factor in the religious conversion process among ethnic Chinese in Belitung, serving not as the initial impetus but rather as the culmination of an extended period of religious exploration. Male participants frequently reported earlier exposure to Islamic education and social environments, indicative of a phase characterized by exploration and engagement prior to formalizing their religious commitment through marriage. Conversely, female participants appeared to be more profoundly influenced by cultural norms emphasizing spousal loyalty and the legal-religious frameworks governing marriage in Indonesia. Negara menjamin ekspresi keagamaan setiap warga negara, apapun keyakinannya. Paradoksnya, kebebasan beragama di Era Orde Baru dibatasi, khususnya kepada keturunan Tionghoa. Orang Tionghoa tidak diperbolehkan untuk mengekspresikan ketionghoaan mereka dalam bentuk apapun, termasuk agama. Mereka harus mengidentifikasi kembali agama mereka menjadi salah satu dari lima agama resmi pada saat itu. Untuk memudahkan proses administrasi, salah satunya perkawinan, mereka mengonversi agama menjadi salah satu agama yang diakui negara. Artikel ini menyoroti sejauh mana keyakinan dan cinta saling berkaitan dalam pengalaman konversi agama ke Islam para etnis Tionghoa di Belitung. Dengan menggunakan teknik sampeling bola salju, kami melakukan wawancara individu semi terstruktur dengan 15 etnis Tionghoa Belitung yang berusia 30 hingga 63 tahun. Narasumber adalah orang Tionghoa yang memilih untuk melakukan konversi agama ke Islam, setelah disahkannya Konfusianisme. Temuan menunjukkan bahwa pernikahan memainkan peran yang menentukan dalam konversi agama etnis Tionghoa di Belitung, bukan sebagai penyebab utama tetapi sebagai puncak komitmen dalam proses eksplorasi agama yang lebih panjang. Peserta laki-laki sering mengalami paparan lebih awal terhadap pendidikan Islam dan lingkungan sosial, mencerminkan tahap pencarian dan pertemuan sebelum mengukuhkan komitmen mereka melalui pernikahan. Sebaliknya, peserta perempuan lebih kuat dipengaruhi oleh ekspektasi budaya akan kesetiaan kepada suami dan kerangka hukum-agama pernikahan di Indonesia.